2013
DOI: 10.1111/cogs.12022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Implicit Learning in Syntactic Comprehension

Abstract: This study provides evidence for implicit learning in syntactic comprehension. By reanalyzing data from a syntactic priming experiment (Thothathiri & Snedeker, 2008), we find that the error signal associated with a syntactic prime influences comprehenders' subsequent syntactic expectations. This follows directly from error-based implicit learning accounts of syntactic priming, but it is unexpected under accounts that consider syntactic priming a consequence of temporary increases in base-level activation. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
137
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 66 publications
18
137
2
Order By: Relevance
“…Thus, it appears that the inverse frequency effect that is taken as evidence for implicit learning accounts of structural priming should be evaluated based on an assessment of individual-level structural preferences. Jaeger and Snider (2013;Fine & Jaeger, 2013) present an extensive discussion of implicit learning-based accounts of structural priming, and argue that the predictions of these accounts should rest on nuanced, contextual information about individual language users, rather than population-level estimates of an individual's linguistic experience. Our data add weight to this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that the inverse frequency effect that is taken as evidence for implicit learning accounts of structural priming should be evaluated based on an assessment of individual-level structural preferences. Jaeger and Snider (2013;Fine & Jaeger, 2013) present an extensive discussion of implicit learning-based accounts of structural priming, and argue that the predictions of these accounts should rest on nuanced, contextual information about individual language users, rather than population-level estimates of an individual's linguistic experience. Our data add weight to this claim.…”
Section: Discussionmentioning
confidence: 99%
“…As Jaeger and Snider (2013;Fine & Jaeger, 2013) point out, average production frequencies (such as corpus estimates of DO and PO frequency, or the base rates that we derive from the Pre-bias phases of our experiments) may not appropriately capture the linguistic experience and expectations of individual speakers. They further note that implicit learning accounts of structural priming suggest that nuanced information about the prior experience of individual speakers should be more valuable in predicting subsequent production performance (such as the effects that our Bias phases have on DO and PO production) than population-or sample-wide estimates of an individual's production experience.…”
Section: Analysis Based On Individual Base Rates Of Do Productionmentioning
confidence: 98%
“…This suggests that the experimental context in which a task is performed can also influence cue-weighting. Recently, Jaeger and colleagues (Fine & Jaeger, 2013) have shown that over the course of a single experiment listeners can adapt to the frequency of certain syntactic structures in the linguistic environment, resulting in changes in syntactic processing. Additionally, in studies of lexical recognition, participants' speed and accuracy are affected by the type and number of real or nonwords in the experimental context; these findings have been accounted for in models of speech perception which incorporate attentional modulation (e.g., Mirman, McClelland, Holt, & Magnuson, 2008;Pitt & Szostak, 2012).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…For example, Jaeger and Snider (2013) found stronger priming when DOD-biased prime verbs were presented in PD prime structures, and Bernolet and Hartsuiker (2010) reported stronger priming when primes with PD-biased verbs were presented in DOD-structures in Dutch. Fine and Jaeger (2013) reanalysed Thothathiri and Snedeker's (2008b) comprehension study and found that prime structures that were more surprising led to stronger expectations that that same structure would also be used in the target sentence. Jaeger and Snider referred to this as prime surprisal since participants were more likely to be primed when the co-occurrence of the prime verb and prime structure was unexpected.…”
Section: Introductionmentioning
confidence: 99%